Determining Factors of Prosocial Behavior in Adolescents in Semarang City - Pratiwi, Margaretha Maria Shinta; Utami, Retno Ristiasih; Yasin, Mohd Hanafi Mohd; Arifin, Afriza Animawan; Zuliyanti (Psympathic : Jurnal Ilmiah Psikologi, 2025)
The determinants of adolescents' prosocial behavior prioritize the welfare of others. In this context, cooperation (gotong royong), as a reflection of prosocial behavior, is a core cultural value and part of Indonesian identity. This research aims to examine the role of empathy in mediating the relationship between peer social support and democratic parenting styles with adolescents' prosocial behavior. A quantitative survey was conducted using several instruments, namely Scenario-Based Prosocial Intention Questionnaire (SBPIQ), Empathy Scale, Parental Democratic Parenting Scale, and Peer Social Support Scale. This research included 621 adolescents aged 12–18 years in Semarang, selected through convenience sampling. Data were analyzed using CB-SEM with Mplus software version 8.3. The results showed that democratic parenting styles, peer social support, and empathy significantly influenced prosocial behavior. Furthermore, empathy played a mediating role in the relationship between parenting styles and peer support with adolescents' prosocial behavior.